Cervical lymph node FNAC: a simple and sensitive tool to diagnosis malignancies - Majal G. Shah; Deepak K. Goel; Trupti S. Patel; Priti P. Trivedi (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Fine needle aspiration cytology (FNAC) of a lymph node is a simple screening and diagnostic tool to diagnose malignancies both primary as well as secondary which not only confirms the presence of metastatic disease, but also suggests regarding the nature and origin of the primary tumour. It is a well-tolerated, cost effective, almost free of complication procedure and reproducible which helps to diagnose and monitor the recurrence of malignancies.Aim: To assess the various malignant causes of cervical lymphadenopathy through FNAC. Design: A retrospective record based cross-sectional study of 125 patients with enlarged cervical lymph nodes diagnosed to have primary or secondary lymph node malignancy by cytology and confirmed by histopathology and immunohistochemistry wherever required.Materials and Methods: The material was obtained from patients, having enlarged cervical neck node over a period of one year in cytology laboratory of the Department of Pathology, Gujarat cancer research institute. Cervical lymph nodes were aspirated, and smears were prepared & processed following standard techniques. Data was collected, tabulated and then analysed.Results: In this study,125 cases of cervical lymphadenopathy were analysed. Male were affected much more commonly than females in the ratio of approximately 9:1. The most common age of presentation was fifth and the sixth decade. Most common malignancy to be diagnosed was squamous cell carcinoma. Most common primary site was oral cavity.Conclusion: FNAC is a quick, convenient and safe method for diagnosis of suspected / unsuspected metastatic and recurrence of malignancy in neck nodes.